Normative Wideband Tympanometry Measures in Birth to 2-Months Iranian Infants: A Preliminary Study - Ebrahim Stajloo; Hassan Haddadzade Niri; Mohammad Maarefvand; Malihah Mazaheryazdi (Auditory and Vestibular Research)
Background and Aim: Wideband Tympanometry (WBT) evaluation of the middle ear is a more accurate approach to identifying middle ear disorders, especially in infants and neonates. Therefore, the need to achieve WBT normative values in the infant population seems obvious. This study aims to evaluate the normative wideband tympanometry values measured in birth to 2-months Iranian infants. Methods: Sixty-four infants participated in this study, including 9 girls and 11 boys in the age group of 0–14 days and 17 girls and 27 boys in the age group of 15–60 days. Results: The normative range of the mean resonance frequency in the first and second age groups was between 298–323 Hz and 324–339 Hz, respectively. At the frequencies of 500 Hz and 1000 Hz, the effect of age groups, at the frequency of 2000 Hz, the effect of age groups, gender, and ear side, at the frequency of 6349 Hz, the effect of gender and age groups, and finally at the frequency of 8000 Hz, the effect of gender in different modes was observed. The normative range of the mean ear canal volume in the first and second age groups was between 0.41–0.38 ml and 0.42–0.46 ml, respectively. The normative range of mean peak tympanometric pressure in the first and second age groups was between –21 to 32 daPa and –8 to 25 daPa. Conclusion: The use of separate norms for males and females in different situations may increase the sensitivity and specificity of the wideband tympanometry.